2008
DOI: 10.1021/jp806708z
|View full text |Cite
|
Sign up to set email alerts
|

CCVD Synthesis of Single- And Double-Walled Carbon Nanotubes: Influence of the Addition of Molybdenum to Fe−Al2O3 Self-Supported Foams

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…The conditions required for the formation of DWNTs and SWNTs have been investigated independently. These include catalyst particle size [25][26][27], carbon source flow rate [28], catalytic material composition [29], and tempera- ture [26,30]. However, there are some contradictions between these studies, as the parameters are not always investigated at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…The conditions required for the formation of DWNTs and SWNTs have been investigated independently. These include catalyst particle size [25][26][27], carbon source flow rate [28], catalytic material composition [29], and tempera- ture [26,30]. However, there are some contradictions between these studies, as the parameters are not always investigated at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra were fitted with quadrupolesplitting distributions (QSD) assuming a linear correlation between the isomer shift and quadrupole splitting, which will not be discussed here, similar spectra having been extensively discussed elsewhere. 66 A Mössbauer spectroscopy study of similar specimens revealed that there is no interaction between iron-and molybdenum species 34 and comparing with the data obtained for a γ-(Al/Fe) 2 O 3 solid solution 67 could indicate that the present doublet represents Fe 3+ ions distributed among the tetrahedral and octahedral lattice sites of γ-Al 2 O 3 , a defective 9 spinel structure, thus revealing the formation of a γ-(Al/Fe) 2 O 3 solid solution. More specific details about the Fe 3+ -cation distribution in the spinel structure cannot be concluded from the present spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe/Mo molar ratio was fixed to 5 for all samples. The addition of different amounts of molybdenum to the Fe−Al 2 O 3 system was investigated in an earlier study, 34 which showed that the addition of a small amount of molybdenum first favors the formation of DWCNTs over that of SWCNTs and, second, activates smaller nanoparticles, thus producing smaller-diameter CNTs. Each "as-prepared" powder was divided into two batches.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For F (Figure 5a), the proportion of single-walled carbon nanotubes is close to 70%, but for FM (Figure 5b), it is much lower (close to 50%), whereas the proportion of double-walled carbon nanotubes has increased to 40%, in agreement with earlier results. 23 17,28 where this proximity resulted in a higher selectivity toward single-walled carbon nanotubes. It is also noteworthy that, for a given sample, the average inner diameter of the double-walled carbon nanotubes is equal to or lower than the average diameter of the single-walled carbon nanotubes, supporting the yarmulke mechanism, 35,36 a basegrowth mechanism according to which the second nanotubes' cap is formed underneath the first one during the nucleation stage that precedes the simultaneous growth of the two walls.…”
Section: Resultsmentioning
confidence: 99%